Registro e uso da marca como ferramenta de gestão da Cooperativa Agroindustrial extrativista das mulheres do município de Cametá - Pará - SILVA, Saulo Rafael Silva e (2019)
Solidarity economy enterprises are increasingly in need of management tools for the development of their businesses, including tools that assist in the creation and dissemination of the visual identity, since most still commercialize their products and offer their services without differentiating from other competitors, practices which could be softened with the correct use of a brand. In order to confront this debate, the present work aimed at the realization of a study of the registration and use of the brand applied to the enterprises of solidarity economy aiming at the aggregation of value to the products and services offered with regional characteristics, through a methodological process of the case study in a cooperative of family farming constituted only by women, in the Amazon. The analysis was based on a theoretical framework that sought to discuss the innovation processes that stimulated rural development, family agriculture, cooperativism and women's participation in this context, as well as a detailed study on the registration and use of brands as a tool for management for adding value to a business, including enterprises that work with family farming products. To carry out the field research, it was made the choice of the agroindustrial and extractive cooperative of the women of the municipality of Cametá. Initially, the cooperative was diagnosed about the operation, challenges, brand use and strengthening strategies. From then on, an analysis was made of the new COOPMUC brand proposal, approved by the members, to verify the fulfillment of all the necessary requirements for the registration of the brand. With this step the protocol of the registration of the brand COOPMUC was made to be used as tool of aggregation of value to the products and services offered by the enterprise. Finally, it was identified that the cooperative has several positive attributes for the valorization of its brand, for that it is necessary that marketing actions are constructed aiming to give visibility to the products and services added to the brand and thus bring to the knowledge of the final consumers the advantages and differentials of the enterprise.